Practical aspects of antiseizure medication treatment in pediatric patients: A helpful guide for pharmacists counseling young patients with epilepsy and their parents - Pecikoza, Uroš; Nastić, Katarina (Archives of Pharmacy, 2025)
Epilepsy is a common brain disorder which frequently affects pediatric patients (from newborns to adolescents). The cornerstone of epilepsy treatment for most patients is the use of antiseizure medicines (ASM). These medications, when used as monotherapy or in combination, can achieve seizure control in up to 70% of patients with epilepsy. However, despite the availability of effective ASMs, adherence to these medicines in pediatric epilepsy tends to be suboptimal, which may adversely affect the long-term prognosis of pediatric patients. In this regard, pharmacist-led interventions, aimed at increasing the health literacy of patients and their family members regarding epilepsy treatment, have been shown to increase adherence to the prescribed ASMs. These interventions focus on educating patients and parents on the nature of epilepsy and practical aspects related to appropriate ASM use. In this article, we aimed to provide a useful source of information for pharmacists (and other healthcare workers) on how to counsel patients and parents on issues related to starting/using ASM treatment (e.g. appropriate dose titration, managing skipped doses), additional measures that may improve treatment outcomes (e.g. monitoring seizure frequency, avoidance of seizure triggers) and safety risks associated with ASMs (and how to control/mitigate these risks).
Keywords: pediatric epilepsy; epileptic seizure; antiseizure medication; pharmacist-led intervention